Evaluation of anti-bovine anti-equine and recombinant protein A/G horseradish peroxidase conjugates for cross reactivity to wildlife serum antibodies using ELISA - Crafford, Jan Ernst (University of Pretoria, 2018)
Dissertation (MSc)--University of Pretoria, 2017.